Lorenzo Palacios, Chacalón: el ídolo popular en el siglo XXI - Quispe Lázaro, Arturo (Pontificia Universidad Católica del Perú, 2023)
In this article, I will address the social and cultural processes involved in the shaping and popularity of the popular idol of Peruvian tropical music chicha , «Papá Chacalón.» He was a singer who emerged from the most marginalized sectors of Lima society. Among his followers are mayors, prisoners serving their sentence in jail, as well as men and women from the poor neighborhoods of Lima. Several decades after his death, there is a new legion of fans, «chicheros chacaloneros» (Chacalón’s followers). The popular idol, in this context, is configured based on and from the daily relationship between Chacalón and his followers. In this work, I will place special emphasis on the idol-follower relationship, the forms of social interaction, and the cultural assessments involved. I will posit that the ideas of equality and social recognition are central elements in the construction of «Papá Chacalón» as a popular idol and his continuity in the 21st century. This is an ethnographic work carried out during the anniversary festivities of Chacalón, held on April 26 (his birthdate) and June 24 (the day of his death), which also addresses how his followers organize around those dates.

En este artículo, abordaré los procesos sociales y culturales que intervienen en la configuración y vigencia del ídolo popular de la música tropical peruana chicha, «Papá Chacalón». Él fue un cantante que surgió de los sectores más marginados de la sociedad limeña. Entre sus seguidores se encuentran alcaldes, presos que purgan condena en cárceles, así como hombres y mujeres de los barrios de Lima. A varios lustros de fallecido, hay una nueva legión de fans, de «chicheros chacaloneros». El ídolo popular, en este contexto, se configura a partir y desde la relación cotidiana entre Chacalón y sus seguidores. En este trabajo, pondré especial énfasis en la relación ídolo-seguidor/a, en las formas de relación social y las valoraciones culturales que intervienen. Sostendré que las ideas de igualdad y reconocimiento social son elementos centrales en la construcción de «Papá Chacalón» como ídolo popular y su continuidad en el siglo XXI. Este es un trabajo etnográfico llevado a cabo en las festividades de aniversario de Chacalón realizadas el 26 de abril (día de su nacimiento) y el 24 de junio (día de su fallecimiento), que aborda también la organización de sus seguidores en torno a estas fechas.
Lorenzo Palacios, Chacalón: A Popular Idol of the 21st Century
Keywords: Peruvian tropical music Chicha; Papá Chacalón; Popular idol; Peruvian cumbia; Popular music; Sociology of music; Música tropical peruana Chicha; Papá Chacalón; Ídolo popular; Cumbia peruana; Música popular; Sociología de la música; https://purl.org/pe-repo/ocde/ford#5.04.03